2023
DOI: 10.4108/eetsis.3843
|View full text |Cite
|
Sign up to set email alerts
|

Comments Analysis on Social Media: A Review

Brian Alafwan,
Manahan Siallagan,
Utomo Sarjono Putro

Abstract: As the number of people using and participating in social media grows, academics become interest in studying this new media, specifically comment analysis, in order to comprehend public opinion and user behavior. However, there are no studies that map the development of comment analysis domain, which would be valuable for future research. To address the issue, we examine prior publications using PRISMA approach, and offer suggestions for further research. An investigation was conducted to locate pertinent publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 170 publications
(46 reference statements)
0
0
0
Order By: Relevance
“…In comparison to surveys, social media appears to be a more suitable source for a better and more comprehensive understanding of public perception. This is because surveys tend to represent the perspective of a small group of individuals rather than capturing the overall public opinion or societal views [37]. Additionally, due to the time and high capital costs involved in the data collection process for surveys, the quantity of data is often limited.…”
Section: The Use and Impact Of Social Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison to surveys, social media appears to be a more suitable source for a better and more comprehensive understanding of public perception. This is because surveys tend to represent the perspective of a small group of individuals rather than capturing the overall public opinion or societal views [37]. Additionally, due to the time and high capital costs involved in the data collection process for surveys, the quantity of data is often limited.…”
Section: The Use and Impact Of Social Mediamentioning
confidence: 99%
“…Instagram data are rarely used in studies, both due to API usage requirements and privacy policies. When examining 115 studies related to sentiment and content analysis published between 2010 and 2022, it is observed that only 30 of these studies are related to sentiment analysis, and a total of 36 studies used YouTube comments [37]. In our study, data were collected from YouTube due to the abundance of technical comments, the absence of character limits, and the ease of accessing past data related to the topic.…”
Section: The Use and Impact Of Social Mediamentioning
confidence: 99%